Ornate Doorknob - Unknown:::Creator::::::::::::
Number 4 of 10 Steinbeck locations: A close up of ornate door handle with an inscription on back reading, East of Eden. Others in this series are numbers. 0-064, 0-809, 0-810, 0-812, 0-813, 0-814, 0-815, 0-816, 0-817.